2018
DOI: 10.1111/aor.13286
|View full text |Cite
|
Sign up to set email alerts
|

Neomyogenesis in 3D Dynamic Responsive Prosthesis for Inguinal Hernia Repair

Abstract: Despite undisputed improvements, prosthetics hernia repair continues to be affected by unacceptable rates of complications. Postoperative adverse events such as discomfort and chronic pain represent a subject of increasing concern among the surgical community. Poor quality biologic response, stiff scar plates, and mesh shrinkage, a typical effect of conventional static meshes and plugs, are all indicated as the main reasons for many of the complications related to inguinal hernia repair. Even the conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Made of the same polypropylene material as conventional meshes and owing an intrinsic centrifugal expansion, this inguinal hernia device, named ProFlor, is intended to be inserted fixation free into the defect thus achieving permanent obliteration. Recent literature has demonstrated that the dynamic compliance of this 3D hernia scaffold allows for a totally different biological response achieving development of newly formed connective tissue, vessels, nerves and muscle bundles, to full maturation [20][21][22][23] . The pathogenetically and physiologically coherent therapy model embodied by this 3D hernia device is diametrically opposed to the concept of reinforcing the groin with fibrotic mesh incorporation, which has been widespread for more than half a century.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Made of the same polypropylene material as conventional meshes and owing an intrinsic centrifugal expansion, this inguinal hernia device, named ProFlor, is intended to be inserted fixation free into the defect thus achieving permanent obliteration. Recent literature has demonstrated that the dynamic compliance of this 3D hernia scaffold allows for a totally different biological response achieving development of newly formed connective tissue, vessels, nerves and muscle bundles, to full maturation [20][21][22][23] . The pathogenetically and physiologically coherent therapy model embodied by this 3D hernia device is diametrically opposed to the concept of reinforcing the groin with fibrotic mesh incorporation, which has been widespread for more than half a century.…”
Section: Discussionmentioning
confidence: 99%
“…These adverse phenomena do not occur in ProFlor that, positioned fixation free to permanently obliterate the defect, moves in tune with the inguinal backwall. Lastly, ProFlor does not shrink because its intrinsic dynamic responsivity induces a unique biologic response with development of newly formed vessels, nerves and muscle fibers characterizing this 3D device as a regenerative scaffold [20][21][22][23][24] . These proprietary features of ProFlor embody a substantial difference to patch and plug technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giuseppe Amato et al of the University of Cagliari, Cagliari, Italy, reported on a 3D dynamically responsive implant for inguinal hernia repair. It is a multilamellar shaped prosthesis, intended to be placed fixation‐free.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…20 The ingrowth of viable connective tissue, newly formed muscles, and mature nerves in the 3D device has already been histologically demonstrated in humans. 21,22 However, to support and maintain the function of these newly ingrown and highly specialized tissue components the presence of specific growth factors promoting a contextual development until full maturation of a suitable vascular network is crucial. The scope of the present study is to demonstrate this specific feature of the 3D hernia device.…”
Section: Introductionmentioning
confidence: 99%